Efektivitas Media Audio Visual Dalam Pembelajaran Sejarah Kebudayaan Islam terhadap Hasil Belajar Siswa di MTs Badru Tamam - Nurkholis Imam Ikhsan; Fahmi Irfani; Ibdalsyah Ibdalsyah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Learning media are all forms in the form of tools and objects that can help the learning process by stimulating thoughts, bringing feelings, to growing students' attention and willingness to further explore the material presented so as to create learning conditions that are intentional, orderly, purposeful, and effective. under control. The history of Islamic culture itself consists of 3 words, each of which has a meaning, namely, history, culture, and Islam. In Arabic history is called tarikh / date, which is a branch of science that deals with various events. The meaning of history is all forms of past events that have important value in the human journey. This Audio Visual Learning Media is present because there is less than optimal learning. And one of the subjects that really need it is the History of Islamic Culture. The research method used by the researcher is descriptive method. Descriptive method is a method or method used in analyzing research data by clearly describing or describing the data that has been collected as it is. Based on the results of product moment statistical analysis, there is a positive correlation between variable X and variable Y, which includes a strong correlation between audio-visual media in SKI learning and learning outcomes. The teacher applies learning and students can get good learning so that students are able to develop their talents and can improve their attitudes and behavior after receiving learning from the teacher. Student learning outcomes can also be obtained properly influenced also by the conditions of students that allow them to participate in the teaching and learning process, such as physical health, school environment, and community environment. Keywords: Effectiveness, Audio Visual Media, History of Islamic Culture